Estimating population immunity to poliovirus in Lebanon: Results from a seroprevalence survey, 2016. Issue 31 (26th June 2020) - Mansour, Ziad; Said, Racha; Wannemuehler, Kathleen; Weldon, William; Estephan, Joe; Khachan, Joseph; Warrak, Ramy; Hendley, William; Ehrhardt, Derek; Farag, Noha H.
Highlights: This is the first study to assess the seroimmunity against polioviruses in Lebanon. Seroprevalence for all three poliovirus serotypes was greater than 90%. Coverage on cards or by parental recall was lower than the seroprevalence findings. Sustaining the immunity levels is essential to prevent polioviruses transmission. Standardizing card formats is needed to guarantee the vaccination records accuracy. Abstract: Introduction: Circulation of poliovirus in neighboring countries and mass population movement places Lebanon at risk of polio and other vaccine-preventable disease outbreaks. Determining population immunity levels is essential for guiding program planning and implementation of targeted supplementary immunization activities (SIAs) in governorates and subpopulations with low seroprevalence. Methods: A cross-sectional multi-stage cluster survey was conducted during February-December 2016 in all six governorates of Lebanon adapted from the World Health Organization (WHO) recommended Expanded Progamme on Immunization (EPI) methodology. Sera from selected children aged 12–59 months were tested for poliovirus neutralizing antibodies. Results: Of 2, 164 children recruited in this study, 1, 893 provided sufficient quantity of serum samples for laboratory testing. Seroprevalence for all three poliovirus serotypes was greater than 90% in all six governorates. Poliovirus vaccine coverage with three or more doses, based on vaccination cards or parental recall, ranged between 54.1% for children aged 36–47 months in the North and 83.5% for children aged 48–59 months in Beirut. Conclusion: Immunity to polioviruses was high in Lebanon in 2016 following a series of supplementary immunization activities. It is essential to continue strategies that increase vaccination coverage in order to sustain the considerably high immunity levels and prevent reintroduction and transmission of poliovirus. Educating caregivers and training health care workers on the standardized usage of home-based vaccination records is needed to guarantee the accuracy of records on children's vaccination status.